“The doctors and nurses looked like aliens’: a qualitative study on the subjective hospitalization experiences of severe COVID-19 patients in Slovakia“ - Peter Halama; Jana Tencerová; Branislav Uhrecký (International Journal of Qualitative Studies on Health & Well-Being)
Due to the need to hospitalize a large number of patients during the COVID-19 pandemic, the psychological conditions of hospitalized patients were often overlooked. This study focuses on the qualitative analysis of the subjective experiences of patients with a severe COVID-19 disease in Slovakia during hospitalization. A total of 27 Slovak participants (11 men and 16 women, mean age 57.10 years) who were hospitalized with severe COVID-19 disease were interviewed about their subjective experiences during hospitalization. The data was analysed using thematic analysis. The main themes included negative emotions such as distress, discomfort with the illness, discomfort with the medical environment and helplessness. The main sources of distress were the sense of isolation, witnessing the death of another patient, own death concerns, and concerns for others. Sources and strategies used by patients to improve their mental state included interpersonal resources such as contact with relatives and friends, instrumental support from them, mutual help among patients and professional psychological support. Interpersonal resources included optimism, hope, religion and spirituality, recollection of significant others, and reconciliation with the possibility of death. The results have implications for medical staff as they help them to understand the psychological state of COVID-19 patients during hospitalization and can inform psychological interventions to improve hospital care for these patients.